ALIRAN JABARIAH DAN QODARIAH BESERTA PEMIKIRAN PARA TOKOHNYA - Surya, Diva Maylana; Shomad, Abdus; Mahfuzah, Noor (Tarbawi, 2024)
Aqidah is the main aspect of Islamic teachings preached by the Prophet Muhammad. This is clearly visible in the Prophet's main mission to spread Islam in Mecca. The Aqidah aspect is an issue that is quite important than the Sharia and is clearly visible in the Qur'an which explains a lot about faith. After the death of the Prophet Muhammad, the Islamic community experienced a split in several sects, namely after the death of Caliph Usman bin Affan and after the murder of Ali Bin Abi Talib. The sects in Islam emerged because of the many different thoughts of figures, for example thoughts about the power of Allah and human will, the position of revelation. and reason, God's justice. And in the end various sects emerged such as Jabariah, Qodariah, Shi'ah, Kkhuarij, Murjiah and others. This was said by the Prophet that the Islamic community would split into several groups. Qadariah is a sect founded by Ma'bad Al-Juhani, Gaila al-Dimasyqi, and the followers of Wasil ibn' Atha, Umar bin Ubaud, they believe that humans have freedom in their actions, where there are no demands or wills of God in their affairs. Some of these groups believe that human deeds or actions are not God's will And the background to the birth of genre Jabariah is still unclear. And the opinion of Abu Zahra says that this sect emerged from the time of the Companions and the time of the Bani Umayyh. At that time the ulama were discussing the issues of Qada, Qadar, and human power. This sect was founded by Jahm bin Afwan and Ja'ad bin Dirham. This research discusses sects or schools of Islam with conflicting thoughts, namely the idea of God's power over humans and the thought of Qada and Qodar. Because studying the meaning of these two schools is very important for us to be careful and be able to lead someone to strong-founded beliefs. The aim of this research is to address the wisdom of differences in thinking regarding Qoda and Qodar beliefs. The method used is the Leatherface Method by collecting sources from literature. The results of this research show that Muslims are no longer confused or lost with the teachings of deviant sects.